The Collision of New Media Era and Chinese Culture: 新媒体时代与中华文化的碰撞 - Qian , Yujie (Mandarinable: Journal of Chinese Studies, 2000)
In the new media era, it is more closely connected to the whole world, so Chinese culture presents a different charm. The new media provides a channel of “going in” and “going out” to Chinese culture, which has both beneficial and negative impacts. So it’s better to seize the opportunity to make good use of new media technology, to highlight the diversity and uniqueness of Chinese culture, and also to promote Chinese culture and new media colliding with a wonderful spark.